Kinematic analysis of the equestrian — Walk, posting trot and sitting trot - Schils, S. J.; Greer, N. L.; Stoner, L. J.; Kobluk, C. N. (Human Movement Science, 1993)
The purpose of this study was to determine if significant differences existed between skill levels of riders at selected gaits. A high-speed video system analyzed the relative angles of the shoulder, hip and knee and the absolute angles of the upper arm, trunk, thigh and lower leg of 63 subjects at three levels of expertise; beginning, intermediate and advanced. Subjects performed at three gaits; walk, posting trot and sitting trot. Significant differences were found between the levels of riders for all angles, except the knee (p<0.05). Significant differences were also found between all gaits for all angles, except the shoulder (p<0.05). Descriptive statistics determined that the advanced rider positioned the upper body closest to the vertical and carried the upper arm furthest from the trunk.